1997
DOI: 10.1021/ie970237c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evidence of the Multiplicity Mechanism in Methyl tert-Butyl Ether Reactive Distillation

Abstract: The existence and explanation of steady-state multiplicity in methyl tert-butyl ether (MTBE) reactive distillation have been addressed by several authors. Recently, Schrans et al. (Comput. Chem. Eng. 1996b, 20, S1609−S1614) analyzed the dynamic behavior of a rigorous dynamic model and verified the presence of multiple solutions. This paper shows how the mechanistic explanation given by Hauan et al. (Ind. Eng. Chem. Res. 1995, 34 (3), 987−991) may be used to interpret and predict dynamic behavior when the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Surprisingly, even the nonreactive binary mixture methanol-isobutene showed similar oscillations, and the authors associated the thermodynamics of this binary mixture with the occurrence of the oscillations. Oscillations for feed composition steps and steady-state multiplicities for the reactive MTBE system have further been demonstrated by dynamic simulations of the Nijhuis column (Schrans et al, 1996;Hauan et al, 1997). Schrans et al (1996) first reported that there are three steady states possible for the MTBE system, two of them stable and one unstable.…”
Section: Multiple Steady States In Reactive Distillationmentioning
confidence: 94%
“…Surprisingly, even the nonreactive binary mixture methanol-isobutene showed similar oscillations, and the authors associated the thermodynamics of this binary mixture with the occurrence of the oscillations. Oscillations for feed composition steps and steady-state multiplicities for the reactive MTBE system have further been demonstrated by dynamic simulations of the Nijhuis column (Schrans et al, 1996;Hauan et al, 1997). Schrans et al (1996) first reported that there are three steady states possible for the MTBE system, two of them stable and one unstable.…”
Section: Multiple Steady States In Reactive Distillationmentioning
confidence: 94%
“…To understand the mechanism, it is important to consider necessary and sufficient conditions for output multiplicity. Previous authors (e.g., Hauan et al, 1995;Hauan and Lien, 1997) have discussed multiplicity in relation to strongly nonlinear behavior, but nonlinearity is only necessary and not sufficient for output multiplic- ity. Provided that a change in an operating condition is reversible, the bifurcation diagram for that parameter will be smooth and only one steady state will exist.…”
Section: Multiple Steady States In a Mtbe Columnmentioning
confidence: 99%
“…In addition to the above studies, which concern the fundamental causes of multiplicity, mechanistic explanations for multiplicity in hybrid columns have also been proposed (Hauan et al, 1995;Hauan and Lien, 1997). Such discussions are useful for elaborating the changes that occur within columns when undergoing transitions between parallel steady states.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple steady states in reactive distillations were demonstrated by several workers. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The most commonly investigated situations include the methyl tert-butyl ether (MTBE) synthesis in the Jacobs-Krishna 2 column configuration and the tert-amyl methyl ether (TAME) synthesis in the column of Mohl et al. 11 The multiple steady states for these two columns were investigated by Chen et al, 16 who conclude that multiplicities are lost for high values of Da for TAME, while the opposite is found for MTBE.…”
Section: Introductionmentioning
confidence: 99%
“…Of special interest is the existence of multiple steady states in these problems, since the combination of separation and reaction can, in principle, introduce the nonlinearity that can cause multiplicity. Multiple steady states in reactive distillations were demonstrated by several workers. The most commonly investigated situations include the methyl tert -butyl ether (MTBE) synthesis in the Jacobs−Krishna 2 column configuration and the tert -amyl methyl ether (TAME) synthesis in the column of Mohl et al . The multiple steady states for these two columns were investigated by Chen et al, who conclude that multiplicities are lost for high values of Da for TAME, while the opposite is found for MTBE.…”
Section: Introductionmentioning
confidence: 99%